Cultural Remodelling of Refugee Armenians after the Genocide - Paronyan, Shushanik (Armenian Folia Anglistika, 2015)
The present article concerns one of the most painful pages in Annenian history – the Genocide of Armenians in 1915 and its traumatic and tragic outcome – forced migrations and cultural remodelling of ethnic Armenians, those who were able to survive the terrible massacre. The aim of the paper is to discuss how the deported ethnic Western Armenians and their descendants underwent the process of acculturation in the USA, reshaping their ethnic cultural blueprint into Diasporan Armenian cultural tradition. To illustrate cases of cultural remodelling, samples of fictional discourse where the literary heroes present three generations of American Armenians have been examined. The research combines the interpretative frameworks of cross-cultural pragmatics and discourse analysis. The analysis of discourse from cultural perspective allows us to conclude that Diasporan Armenians must have formed a multicultural stratum in the American ethnic patchwork.
Keywords: cross-cultural pragmatics; discourse analysis; cultural remodelling; cultural adaptation; multiculturalism